(untitled) (Colombia Medica, 1986)
Gastric remnant carcinoma occurs in the gastric stump after resection for benign disease. An incidence of one to fifteen percent has been reported ten years after resection, with an increasing incidence in subsequent years. Multiple etiological factors have been implicated, and some histologic features have been proposed as pre-malignant conditions. Diagnosis of gastric remnant carcinoma is usually late, hence careful endoscopic examination ten years after resection is recommended. Good surgical technique and procedures to prevent depends on the stage of the disease, and the prognosis, in general, is poor. A 90 percent five-year survival rate can be expected with a diagnosis at an early stage.